Sustainable Human Resource Management: Building an Adaptive and Inclusive Organizational Culture - Alwinda Manao; Syamsul Hadi Senen (Dinasti International Journal of Education Management And Social Science, 2025)
Organizations are faced with the challenge of remaining competitive and relevant. One important approach that can be used to address these challenges is the implementation of sustainable human resource management (HRM). Sustainable HR management plays an important role in building an adaptive and inclusive organizational culture, which can support innovation, employee engagement, and overall organizational performance. The purpose of this study is to identify how the implementation of sustainable HR management can support the formation of an adaptive and inclusive organizational culture. This research uses the Systematic Literature Review (SLR) method, which includes an analysis of scholarly articles published between 2020 and 2024. The research shows that the implementation of sustainable HR management, which includes inclusive recruitment practices, continuous employee development, high employee engagement, and fair performance evaluation, plays an important role in creating an organizational culture that is responsive to change and promotes inclusion. Organizations that integrate sustainability values in their HR practices were found to be better able to adapt to changes in the external and internal environment.    The implication of these findings is that organizations should proactively adopt sustainable HR practices to ensure long-term success.